2023
DOI: 10.3847/1538-4365/acc181
|View full text |Cite
|
Sign up to set email alerts
|

Multimessenger Characterization of Markarian 501 during Historically Low X-Ray and γ-Ray Activity

Abstract: We study the broadband emission of Mrk 501 using multiwavelength observations from 2017 to 2020 performed with a multitude of instruments, involving, among others, MAGIC, Fermi's Large Area Telescope (LAT), NuSTAR, Swift, GASP-WEBT, and the Owens Valley Radio Observatory. Mrk 501 showed an extremely low broadband activity, which may help to unravel its baseline emission. Nonetheless, significant flux variations are detected at all wave bands, with the highest occurring at X-rays and very-high-energy (VHE) γ-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 122 publications
4
13
0
Order By: Relevance
“…Aleksić et al (2013) found that both one-zone and two-zone SSC models can well reproduce the SED observed by 1ES 2344 + 514 in late 2008. Abe et al (2023) SED of Mrk 421 with a VHE flare observed on 2017 February 4 is better reproduced by a two-zone leptonic model than by a one-zone leptonic model. Sahu et al (2020Sahu et al ( , 2021b, Sahu & Valadez Polanco (2022) found that the one-zone photohadronic model is inadequate to explain the multi-TeV flaring events from the transient extreme HSP-like sources of Mrk 501, Mrk 421, and 1ES 2344 + 514, and they proposed a two-zone photohadronic model as an effective methodology.…”
Section: Comparison With Previous Tev Agns' Studiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Aleksić et al (2013) found that both one-zone and two-zone SSC models can well reproduce the SED observed by 1ES 2344 + 514 in late 2008. Abe et al (2023) SED of Mrk 421 with a VHE flare observed on 2017 February 4 is better reproduced by a two-zone leptonic model than by a one-zone leptonic model. Sahu et al (2020Sahu et al ( , 2021b, Sahu & Valadez Polanco (2022) found that the one-zone photohadronic model is inadequate to explain the multi-TeV flaring events from the transient extreme HSP-like sources of Mrk 501, Mrk 421, and 1ES 2344 + 514, and they proposed a two-zone photohadronic model as an effective methodology.…”
Section: Comparison With Previous Tev Agns' Studiesmentioning
confidence: 83%
“…It should be noted that neutrino events from Mrk 421 and Mrk 501 have not yet been detected by IceCube. These best-fitting numbers of astrophysical neutrino events both correspond to very large p-values, which means that this result can only be treated as a rough upper limit (e.g., Abe et al 2023). The neutrino event rate can be obtained by ( ) ( )…”
Section: One-zone Ssc+pp Modelmentioning
confidence: 98%
“…This mechanism also could yield a log-parabolic flux distribution (Rieger 2019), although this may break the correlation between the γ-ray and synchrotron (e.g., optical-to-X-ray) emissions expected in the framework of the one-zone SSC model (Böttcher & Dermer 2010). Note also that a significant X-ray and LAT-band correlation was found by Abe et al (2023) for the entire period 2008-2020, while this correlation was absent in the separate interval 2017-2020. Similarly, the correlation F XRT − F LAT was also absent during 2014 March-October (Paper I), and the data sets not belonging to these two intervals should be responsible for the positive correlation between these emissions in the entire period 2008-2020.…”
Section: Log-normality and Mwl Correlationsmentioning
confidence: 94%
“…Mkn 501: This well-studied, bright TeV blazar has exhibited violent flux variability across the electromagnetic spectrum (e.g., Abdalla et al 2019). The TeV band light curve of this source has revealed several episodes of VHE outbursts, with some of them also being detected with various Cherenkov telescopes (see Ahnen et al 2018;Abdalla et al 2019;Abe et al 2023). The estimated TS var parameter suggests the source to be variable in the TeV band.…”
Section: Notes On Individual Objectsmentioning
confidence: 99%